Chromatographic Analysis of Pesticide in Environmental and Food - González-Curbelo, Miguel Ángel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Pesticides persist as a prevailing tool in global agriculture for the management of pest populations and to increase crop yields. Their extensive application may lead to the dispersion of pesticide compounds into the environment, subsequently resulting in their persistence as residues within food products. Consequently, there exists the potential for adverse consequences for non-target organisms and human well-being.In response to this concern, diverse legal frameworks and surveillance programs have been instituted on an international scale, with the overarching objective of regulating pesticide usage by setting forth maximum admissible levels for pesticide residues. Consequently, there arises a pressing need to develop highly selective and sensitive multi-residue analytical methodologies, tailored to the quantification of these residues within complex matrices.This Special Issue is devoted to the analysis of pesticide residues within both environmental and food matrices via chromatographic techniques, including the development and validation of analytical methods, along with the completion of comprehensive monitoring studies.